Tadeusz Czeżowski’s method of analytical description – historical and systematic study - Zinkiewicz, Maciej (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
The paper depicts the evolution (and studies its ground and motivation) of the conception of the method of analytical description of Czeżowski, one of the most important figures of the Lvov-Warsaw School of Philosophy. It portrays Czeżowski as an author, whose voice on relation between theory and experience, as well as language and empirical reality, can be still considered important and significant. Generally speaking, Czeżowski distinguishes between two kinds of methods: the inductive ones and the no inductive, i.e. the method of analytic description. The results of the former are the base of every further scientific activity, from the empirical sciences to philosophy. The method serves, first of all, to define abstract concepts and to precise scientific terms, what allow next to set and to express relations between them. Its application is an indispensable and essential part of process of building every abstract scientific theory. Despite some similarities between Czeżowski’s method and other methods of conceptual analysis, the former is not subjected to the paradox of analysis (what is shown), according to the author of the paper.